2018
DOI: 10.33225/jbse/18.17.674
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Trajectory of Science Learning Motivation in Korean High School Students

Abstract: This research examined longitudinal trajectories of Korean students’ motivation to learn science using group-based trajectory modeling (GBTM). The changes in five motivational constructs were focused in this research: self-efficacy, intrinsic motivation, grade motivation, self-determination, and career motivation. In addition, the relationship between academic track of students and each trajectory group was examined. Using Science Motivation Questionnaire II, data from 255 male high school students were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In a cross-cultural study, Zeyer et al (2013) translated the SMQ for upper secondary students in four countries: Malaysia, Slovenia, Switzerland, and Turkey. Schumm and Bogner (2016) translated the SMQII into German for tenth graders at the college preparatory secondary school level, and Shin et al (2018) translated the SMQII for male Korean high school students. The SMQII was also translated for Chinese high school students by Dong et al (2020).…”
Section: Adaptation Of Smqii For High School Studentsmentioning
confidence: 99%
“…In a cross-cultural study, Zeyer et al (2013) translated the SMQ for upper secondary students in four countries: Malaysia, Slovenia, Switzerland, and Turkey. Schumm and Bogner (2016) translated the SMQII into German for tenth graders at the college preparatory secondary school level, and Shin et al (2018) translated the SMQII for male Korean high school students. The SMQII was also translated for Chinese high school students by Dong et al (2020).…”
Section: Adaptation Of Smqii For High School Studentsmentioning
confidence: 99%
“…The third focus is the “diversification of materials that can be combined”. We examined examples of high school textbooks from South Korea and attempted to develop as many bonding structures as possible. …”
Section: Methodsmentioning
confidence: 99%
“…GBTM has been implemented in empirical studies that investigate trajectory patterns in public health (e.g., Mody et al, 2019) and social science (e.g., Anderson, 2010) but with very few applications to education (e.g., Buckley et al, 2021;Shin et al, 2018). In one of the only studies that focuses on the adolescent population, Shin et al (2018) used data collected using the Science Motivation Questionnaire II from 255 male high school students over five semesters and applied GBTM to examine the longitudinal trajectories of Korean students' motivation to learn science based on five motivational constructs, namely, self-efficacy, intrinsic motivation, grade motivation, self-determination, and career motivation. The results indicated that students shared the same trajectory pattern in self-efficacy increasing at the second semester but gradually decreasing starting from the third semester.…”
Section: The Development Trajectory Approach For Detecting Student He...mentioning
confidence: 99%